Analisis Macam-Macam Zakat Dan Wakaf Dalam Manajemen Filantrofi - Lailatul Zannah; Maslahah Maslahah; Mieke Maylinda; M. Rafi saputra; Mohammad Ridwan (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Zakat and waqf are forms of worship that have two dimensions, namely the vertical dimension, which is a manifestation of a servant's obedience to his rabb. This research is a qualitative research, in accordance with the object of study, this type of research is included in the category of library research.Islamic philanthropy in this case zakat and waqf are regulated by the state in the form of laws. The role of the state is still considered overlapping in some juridical cases in its application considering that the study in this research highlights more juridical aspects. Zakat and waqf are important instruments in Islamic philanthropy that have an important role in helping the poor, improving community welfare, encouraging wealth distribution, cleansing the Self and wealth, increasing piety to Allah SWT and achieving the goals of Islamic philanthropy. Effective and professional management of zakat and waqf will maximize its benefits to achieve these goals.